PURCHASE DECISION FACTORS FROM PRODUCT QUALITY, DESIGN PACKAGING AND PRICE (Study on Dodol Pineapple consumers in East Lampung) - Muntama Muntama; Syaiful Bakhri; Susi Sulastri; Buchori Buchori (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study is to analyze how the relationship between product quality, packaging design, and price with the reasons why people buy products simultaneously or sequentially. The method used is a quantitative descriptive method, or a method that measures the effect of a variable on other variables. Product quality, packaging design, and price are the main variables. A different tertiary variable is the purchasing point of view. The majority of respondents to this survey are Way Kambas Dodol Nanas consumers. There were about 30 responses to the survey. The selective sampling technique used is called purposive sampling. The reliability test uses the Cronbach's Alpha formula and the validity test uses the Pearson Product Moment correlation point.The data analysis technique used in this study is the Classical Assumption Test, Multiple Linear Regression Analysis Test, T test and F test at a significant level of 5%. Data collection was carried out by distributing questionnaires as the main data collection, and supported by interviews and observations. Based on the results of the analysis, it can be concluded that simultaneously the variables of product quality, packaging design and price have a positive effect on purchasing decisions for Dodol Nanas Way Kambas products. Partially the product quality variable has a significant effect on purchasing decisions, the packaging design variable has a significant effect on purchasing decisions, and the price variable has a significant effect on purchasing decisions. Keywords: packaging design, price, purchase decision, product quality